The Effect of Glacier Ablation on Vegetation Coverage - Xu, Chengjin (International Journal of Natural Resources and Environmental Studies, 2024)
The effects of climate change on glaciers, in terms of their scope and conditions, have become increasingly apparent, with serious consequences for various ecosystems, affecting hydrological and terrestrial factors. This paper reviews the existing literature on the complex interaction between glacier retreat and vegetation distribution. In the short term, glacier retreat may promote vegetation expansion by increasing water supply, while in the long term, drought may occur due to glacier depletion, adversely affecting vegetation growth. In addition, glacial meltwater is usually cooler, so the melting of glaciers will also affect the temperature of water resources, thus affecting the growth of vegetation to a large extent. On the one hand, glacier ablation results in the transfer of glaciated rocks and moraines from the glacier surface to the pericardial zone. The former is rich in organic matter and minerals, while the latter can provide parent rock, promote soil development, increase soil nutrients, and expand vegetation colonization. On the other hand, melting glaciers can cause soil erosion and soil depletion, which is not conducive to the growth of vegetation. Melting glaciers will lead to more surface runoff, which will affect soil erosion and even the formation of new terrain, all of which are associated with vegetation growth. The increasing concentration of carbon dioxide in the atmosphere has led to greening on a global scale, creating positive and negative feedback loops in different regions. Therefore, the glacier ablation and its pathways and sub-pathways are affected, so the glacier ablation seriously affects the vegetation distribution. Overall, the effects of glacial retreat on vegetation distribution are very complex. As glaciers continue to retreat globally, understanding these dynamics is critical to predicting future changes in vegetation distribution.